Fabrication techniques and performance of piezoelectric energy harvesters - Md Ralib, Aliza Aini; Nordin, Anis Nurashikin; Salleh, Hanim (2009)
Energy harvesting devices which convert ambient energy to electrical energy has attracted a lot of attention in commercial sectors. Due to the environmental consciousness, energy harvesting devices or so called micro generators promise a cleaner environment by avoiding the usage of batteries. Piezoelectric energy harvesters are the most promising solution because they can efficiently convert mechanical strain to electrical charge without any additional power. This paper presents a comparative study of previous works on the design and fabrication techniques of piezoelectric energy harvester microgenerators. This lead to an understanding of the several crucial factors affecting the performance of the piezoelectric microgenerators.